Gender Patterns in the Use of Physical Violence Against a Violent Partner: Results of a Cross-Sectional Population-Based Study in New Zealand - Fanslow, Janet (Journal of interpersonal violence, 2022)
We examine gendered patterns in the use of violence in response to the partner's violence (?fighting back?). Within each gender, we examined if socio-demographic differences in prevalence were present, and if contextual factors influenced the use of violence against a violent partner. Data from a large, population-based sample of New Zealand adults was used to identify ever-partnered respondents who had experienced physical IPV (n = 407 women, and n = 391 men). Weighted percentages and 95% confidence intervals (95%CIs) were calculated for the use of violence against a violent partner, stratified by gender. Multivariable logistic regression was used to assess the association between each contextual risk factors and the use of violence against a violent partner. For both men and women, at the multivariable level, use of violence against a violent partner was associated with contextual factors related to the abuse. However, for almost all of these variables a higher proportion of women than men experienced the risk factor; for example, a higher proportion of women than men reported having experienced severe IPV (57.6% women; 43.7% men), injuries resulting from IPV (44.5% women, 15.0% men), and fear of a partner (22.7% women, 4.9% men). Women were also more likely to report experiencing other types of IPV (particularly sexual IPV) and were more likely to report that their children were present at the time of violence. These factors contributed to the higher proportion of women who reported fighting back at least once (53.4% of women and 22.3% of men). Health, social, and legal services need to conduct appropriate and thorough assessment of nature and context (current and historical) of the violence that individuals have been exposed to as part of service provision. Assessments need to be carried out with a gender-lens in order to provide comprehensive and appropriate responses.